Surface solar radiation and its association with aerosol characteristics at an urban station in the Indo-Gangetic Basin: Implication to radiative effect. (15th October 2019) - Kumar, Sunil; Srivastava, A.K.; Pathak, V.; Bisht, D.S.; Tiwari, S.
Abstract: Short-wave incoming solar radiation and aerosol optical characteristics were examined at New Delhi, in the western Indo-Gangetic Basin (IGB) for the period from March 2010 to June 2012 to understand their possible association in different sky conditions along with their radiative implications. During the study period, solar radiation varied between 65 and 624 W m −2, with a seasonal mean of 419 ± 34, 328 ± 32, 308 ± 54 and 306 ± 56 W m −2, respectively in the summer, monsoon, post-monsoon and winter periods. Inter-annually, the magnitude of solar radiation was ∼19% and 23% higher during 2012 as compared to 2011 and 2010. Aerosol optical Depth (AOD) varied between 0.11 and 2.4 (mean: 0.69 ± 0.38) whereas Ångström Exponent (AE) was between 0.46 and 1.81 (mean: 0.8 ± 0.28) during the entire study period. The solar radiation was found to be significantly correlated with the AOD (R = −0.22) and AE (R = −0.45). The mean characteristics of solar radiation and aerosol optical parameters were found to differ significantly in different sky conditions, which were used to examine their possible implications to direct radiative effect (DRE). The DRE at the surface was as high as about −19 W m −2 during clear sky day, which was ∼16 and 48 W m −2 higher than that of haze/foggy and dusty days, respectively. Highlights: A significant correlation with AOD (R = −0.22) and AE (R = −0.45) suggests relative impact on reduction in solar radiation. The solar radiation is ∼43% (5%) higher in clear day compared to haze/foggy (dusty) day. AOD (AE) is ∼23% (20%) higher during hazy/foggy day compared to clear day. The DRE is −19 W m −2 during clear day, which is ∼16 and 48 units higher than that of haze/foggy and dusty days.